USM SUSTAINING COOPERATION IN EDUCATION WITH AFRICA-ASIA DIALOGUE 2016 - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 1 November 2016 Universiti Sains Malaysia (USM) through the USM School of Educational Studies (PPIP) would remain committed in ensuring that discussions on issues in local and global education would be continued and research findings to be welldocumented and included into relevant journals for future reference